Case Study Of Pantai Medivest Sdn Bhd. - Yeak, Su Oo (2007)
The objectives of the privatisation of the government hospital support services are to enhance the services to the existing government hospitals. Pantai Medivest Sdn Bhd is borne on this platform and are providing the services covering the southern zone of peninsular Malaysia.